REVITALISASI PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM PERSPEKTIF GAGASAN PENDIDIKAN NASIONAL BUNG HATTA - Putri Hidayati; M. Nursi; Hendrizal; Nurul Hikmah; Ahmad Farhan Alisnaini; Ismarina Rosida (STKIP Subang, 2026)
Character education serves as a fundamental foundation for shaping the personality of elementary school students. However, in practice, character education is often implemented in a normative manner and has not been deeply integrated into the learning process. This article aims to examine the revitalization of character education in elementary schools through the Deep Learning approach from the perspective of Bung Hatta’s national education ideas. This study employs a qualitative approach using a library research method by analyzing relevant literature, including Bung Hatta’s educational thoughts, national education policies, and theoretical as well as empirical studies on deep learning and character education. The findings indicate that Bung Hatta’s educational ideas emphasize the development of individuals with strong character, moral integrity, independence, and a sense of responsibility as citizens. These values conceptually align with the principles of Deep Learning, which focus on meaningful understanding, critical reflection, active student engagement, and the internalization of values within real-life contexts. The integration of the Deep Learning approach with Bung Hatta’s national education ideas has the potential to revitalize character education in elementary schools in a more contextual, holistic, and sustainable manner. Therefore, this approach can serve as a strategic alternative for strengthening the implementation of character education that goes beyond knowledge acquisition and emphasizes the formation of students’ attitudes and noble values.